Post-Reform Defense Sector Legal Policy: The Principle of Civil Supremacy - Sudarto Sudarto; Siti Zaynul Rahmawati (Jurnal Hukum, 2026)
This study examines Indonesia's national defense legal politics in the post-reform era in safeguarding national sovereignty amidst the dynamics of globalization and strategic environmental changes. Utilizing a normative political law research method with a legislative and historical approach, the study analyzes the direction and nature of defense policy through the review of the 1945 Constitution of the Republic of Indonesia (after the amendments), Law No. 3 of 2002 on National Defense, and various related regulations, including policies on budgeting, military force management, and defense sector reform. The findings show that post-reform defense legal politics seeks to assert civilian supremacy over the military, return the Indonesian National Armed Forces (TNI) to its primary defense function, and build a democratic, professional, and accountable defense system. However, policy implementation still faces various challenges, including weak synchronization of legislation, budget limitations and modernization of defense equipment, suboptimal parliamentary roles in legislation and oversight, and high corruption risks in the defense sector. This study recommends strengthening the defense regulatory framework, enhancing the capacity and integrity of the legislative and executive institutions, strengthening the national defense industry, and improving budget governance and transparency as prerequisites for realizing defense legal politics that can ensure national sovereignty and security in a sustainable manner.